Synthesis, Cytotoxicity Evaluation and Molecular Docking Simulation of Some New 4-(3H)-Quinazolinone -Thiadiazole Hybrids as Anticancer Agents - Mohammed Abdulameer Oleiwi, Munaf H. Zalzala, Mohammed Hassan Mohammed, (Pakistan Journal of Medical & Health Sciences, 2022)
A new series of quinazolinone compounds (I–IV) incorporating 1,3,4-thiadiazole moiety were synthesized .The compounds were characterized by ATR-FTIR,1HNMR and 13CNMR. Their in vitro antitumor efficacy was evaluated against two cancer cell lines, a breast cancer cell line (MCF-7), and lung cancer cell line (A549) using MTT assay .Methotrexate (MTX) was used as a positive control. In order to evaluate the selectivity of the tested compounds toward cancer cells, they were tested also against the normal cells using epithelial cells derived from normal human fibroblast (NHF). All the tested compounds showed less toxicity against (NHF) cell lines compared with cancer cell lines. Among the tested compounds, compound I showed the most potent antitumor activity against MCF-7cell lines (IC50:7.832 µM), the comparative IC50 value for methotrexate on these cell lines was (27.325 µM). All compounds exhibited higher antitumor activity against A549 cell lines than methotrexate, the most potent among them was compound III (IC50:6.669µM). The binding pattern of the designed compounds with their target protein ( EGFR kinase) were studied by molecular docking study using GOLD software.